Produção e qualidade de cultivares de batata-doce em função da idade de colheita e épocas de cultivo - ALBUQUERQUE, José Ricardo Tavares de (2016)
The sweet potato constitutes in a source of energy and nutrients of great social importance and economic, mainly for the poorest people in the Northeast of Brazil, participating the supplies of calories, vitamins and minerals in the human diet, also used in animal feed. The determination of the harvest season has great influence on vegetative growth, quality, roots productivity and fitomass production, and its handling allows adjust supply with to demand. The sweet potato planting season can be determined according of climatic elements, such as air temperature, photoperiod and solar radiation, which have influence on the growth, development and productivity of tuberous roots. In that sense, the objective of this study was to evaluate the agronomic performance of sweet potato cultivars in function of the age of cultivation in two times of harvest. Two experiments were installed, the first in the period from February to June (rainy) and the second from July to November (dry). In both experiments, the experimental outlining used was randomized block, in a split plot in 4 repetitions, which the parcels formed by 3 cultivars (ESAM 1, Paraná and Mãe de Família) and the splitplots by 5 harvest times (90, 105, 120, 135 and 150 days after planting). The evaluated characteristics were: length and diameter of roots, total dry mass of roots, total dry mass of aerial part, fitomass production, commercial productivity and commercial roots, classification and commercial roots format. The agronomic characteristics evaluated were: length and diameter of commercial roots, total dry mass of roots, total dry mass of plants, fitomass production, commercial productivity and total commercial roots, classification and commercial roots format. The evaluated quality characteristics were: pH, soluble solids, titratable acidity, total soluble sugars, starch content, pulp firmness, cooking time and vitamin C. A combined analysis of experiments for all the variables was performed. For the characteristics of diameter, total dry mass of roots, commercial productivity of roots, total roots productivity, there was increasing response with increasing harvest age in both cultivation seasons. The roots classification suffered variation of 80-400 g /root, in both cultivation seasons, however the highest values were observed in the second season. The format note 3 it was the most predominant. The characteristics of soluble solids, total soluble sugars and vitamin C, there was increasing response with increasing harvest age in both cultivation seasons. The pH showed reduced responses in both cultures. The cooking time suffered variation according to the harvest age in both cultivation seasons, but the highest values were found only in the first season. The Paraná cultivar was the one that showed the best performance among the cultivars. While the age of harvest at 150 days after planting showed the best agronomic results. The best cultivation season was observed in the 'dry' period.